Outpatient Antibiotic Therapy and Short Term Mortality in Elderly Patients with Chronic Obstructive Pulmonary Disease - Don D Sin; Jack V Tu (Canadian Respiratory Journal)
OBJECTIVES: To determine the association between outpatient use of oral antibiotics and 30-day all-cause mortality following hospitalization in a group of elderly chronic obstructive pulmonary disease (COPD) patients.